Duration of high-pressure metamorphism and cooling during the intraplate Petermann Orogeny - Walsh, A.; Raimondo, T.; Kelsey, D.; Pfitzner, H.; Clark, Christopher; Hand, M. (Elsevier Science BV, 2013)
The Ediacaran–Cambrian Petermann Orogeny, central Australia, is an exceptional example of intraplate orogenesis. It involved sub-eclogite facies metamorphism and extreme basin inversion during the exhumation of Musgrave Province basement from beneath the formerly contiguous Centralian Superbasin. Sensitive High Resolution Ion Microprobe (SHRIMP) U–Pb geochronology of zircon, titanite and rutile, along with Ti-in-zircon thermometry from meta-igneous samples, have been used to determine the timing and duration of high-pressure metamorphism and subsequent cooling associated with this orogenic event. Peak metamorphic temperatures of 720–760°C were attained at 544±7 Ma (U–Pb zircon). Subsequent cooling to 600–660°C by ~521 Ma occurred at a rate of ~2.6–7.0°C Myr− 1, as recorded by the closure of Pb diffusion in titanite. Further cooling to 585–560°C by 498–472 Ma occurred at a rate of 0.9–4.8°C Myr− 1, as recorded by Pb closure in rutile. The duration of tectonism was long-lived (>40 Myr) across the central and western parts of the orogenic system, and deformation occurred in a comparatively warm and weak portion of crust, characterised by regional thermal gradients of 17–26°C km− 1. This proposed duration of tectonism is much longer than that permitted by a shear heating mechanism, which requires an exceptionally short duration of tectonism, and additionally, an overall cold lithosphere characterised by geothermal gradients of ~9°C km− 1.